2015
DOI: 10.1016/j.taap.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome activity is important for replication recovery, CHK1 phosphorylation and prevention of G2 arrest after low-dose formaldehyde

Abstract: Formaldehyde (FA) is a human carcinogen with numerous sources of environmental and occupational exposures. This reactive aldehyde is also produced endogenously during metabolism of drugs and other processes. DNA-protein crosslinks (DPC) are considered to be the main genotoxic lesions for FA. Accumulating evidence suggests that DPC repair in high eukaryotes involves proteolysis of crosslinked proteins. Here, we examined a role of the main cellular proteolytic machinery proteasomes in toxic responses of human lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(64 reference statements)
2
16
0
1
Order By: Relevance
“…14e18 The results of these investigations were contradictory even for the same cell model, and one study has found that the sensitivity of specific mutants depended on the exposure protocol. 14 Genotoxic signaling triggered by FA in human cells occurred only in the S phase, 19,20 which is consistent with the stalling of replication helicases by DNA-attached proteins. 21 However, FA-induced activation of the transcription factor p53 20 and the DNA damage-responsive kinase ataxia-telangiectasia mutated (ATM) 22 showed bellshaped dose dependence, suggesting that FA-treated cells may experience another major stress that becomes dominant at certain exposure conditions even in S-phase cells.…”
supporting
confidence: 62%
“…14e18 The results of these investigations were contradictory even for the same cell model, and one study has found that the sensitivity of specific mutants depended on the exposure protocol. 14 Genotoxic signaling triggered by FA in human cells occurred only in the S phase, 19,20 which is consistent with the stalling of replication helicases by DNA-attached proteins. 21 However, FA-induced activation of the transcription factor p53 20 and the DNA damage-responsive kinase ataxia-telangiectasia mutated (ATM) 22 showed bellshaped dose dependence, suggesting that FA-treated cells may experience another major stress that becomes dominant at certain exposure conditions even in S-phase cells.…”
supporting
confidence: 62%
“…H460 cells express the wild-type p53 transcription factor and displayed normal stress responses to various carcinogens, such as ionizing radiation (Zhang et al, 2006), chromium(VI) (Luczak et al, 2016) and formaldehyde (Ortega-Atienza et al, 2015; Wong et al, 2012). We have previously characterized p53 activation and mechanisms of cell death by Ni(II) ions in this cell line (Green et al, 2013; Wong et al, 2013a), making it well-suited for dissecting potential toxicological effects of HIF-1α.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mammalian cells suggested that the proteasome participates in DPC removal (Baker et al, 2007;Desai et al, 1997;Lin et al, 2008;Mao et al, 2001;Quiñones et al, 2015;Zecevic et al, 2010). Proteasome inhibition prevents the removal of different types of DPCs including trapped topoisomerases I and II and DNA polymerase β (Desai et al, 1997;Lin et al, 2008;Mao et al, 2001;Quiñones et al, 2015), and sensitizes cells to formaldehyde treatment (Ortega-Atienza et al, 2015). Additionally, DPC polyubiquitylation was observed in the case of covalent topoisomerase I cleavage complexes (Desai et al, 1997).…”
Section: Introductionmentioning
confidence: 99%